2022
DOI: 10.4251/wjgo.v14.i9.1622
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for nonalcoholic fatty liver disease-related hepatocellular carcinoma: Lights and shadows

Abstract: About one-fourth of adults globally suffer from nonalcoholic fatty liver disease (NAFLD), which is becoming a leading cause of chronic liver disease worldwide. Its prevalence has rapidly increased in recent years, and is projected to increase even more. NAFLD is a leading cause of hepatocellular carcinoma (HCC), the sixth-most prevalent cancer worldwide and the fourth most common cause of cancer-related death. Although the molecular basis of HCC onset in NAFLD is not completely known, inflammation is a key pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…Anti-PD-L1 & anti-angiogenic immunotherapy (atezolizumab in combination with bevacizumab) is currently the first-line treatment for advanced HCC. A subgroup analysis of survival outcomes based on the trials evaluating the efficacy of ICIs as first-line therapy showed that viral-HCC could benefit from ICIs ( 168 ). However, for non-viral-HCC patients, ICIs were not observed to be superior to sorafenib, which suggested that obesity may be not a positive marker for ICI therapy in HCC.…”
Section: Obesity Impacts Immunotherapy For Hccmentioning
confidence: 99%
“…Anti-PD-L1 & anti-angiogenic immunotherapy (atezolizumab in combination with bevacizumab) is currently the first-line treatment for advanced HCC. A subgroup analysis of survival outcomes based on the trials evaluating the efficacy of ICIs as first-line therapy showed that viral-HCC could benefit from ICIs ( 168 ). However, for non-viral-HCC patients, ICIs were not observed to be superior to sorafenib, which suggested that obesity may be not a positive marker for ICI therapy in HCC.…”
Section: Obesity Impacts Immunotherapy For Hccmentioning
confidence: 99%
“…Analyses of survival outcomes in subgroups evaluating the efficacy of ICIs as first-line treatment revealed a discrepancy between viral HCC and non-viral HCC, including NASH-related HCC. Tremelimumab plus Durvalumab was the only combination of two ICIs tested against sorafenib in the first-line setting, and the only one that showed a relatively higher OS in the non-viral and viral HCC subgroups [ 61 , 62 ].…”
Section: Surveillance and Diagnosis Of Nafld-related Hccmentioning
confidence: 99%
“…Other studies showed that patients with NASH-driven HCC treated with anti-PD1 or anti-PDL1 showed poorer survival than patients with HCC due to other etiologies. Overall, these data show that NASH-HCC is less responsive to immunotherapy due to NASH-related abnormal T cell activation that induces tissue damage and leads to impaired immune surveillance [ 62 ].…”
Section: Surveillance and Diagnosis Of Nafld-related Hccmentioning
confidence: 99%
See 1 more Smart Citation